Research Priority of Gerontic Nursing in Indonesia: findings from a Delphi Study - I Gede Putu Darma Suyasa; Ni Kadek Sutini (Jurnal Keperawatan Padjadjaran, 2021)
While elderly population in Indonesia continues to increase, research around elderly and health care for elderly is still limited. The purpose of this study was to identify priority of research area on Gerontic Nursing in Indonesia. This was a descriptive study, using Delphi study with 2 survey rounds. Round 1 involved 34 participants purposely selected among nurses who worked in the area of and had a research interest in Gerontic Nursing. Open ended online questionnaire about priority areas was sent to potential participants. Data was analyzed for its similarity, resulted in 36 research areas around Gerontic Nursing. Round 2 involved 204 nurses with the same criteria as in round 1, selected using convenience sampling technique. Close ended questionnaire using Semantic Differential Scale ranged from 1 to 9 was sent online to potential participants. Data was descriptively analyzed for median, interquartile range (IQR), and range. Findings indicated 10 levels of research priority. Level 1 research priority with median of 9, IQR 1, and range 5 were long term care for elderly, family knowledge on caring for elderly, personal hygiene in elderly, competency of Gerontic Nurse, and nutrition in elderly. Nurse academics and researchers are suggested to collaborate with nurse practitioners in various settings to conduct research on these priority areas.